In-vivo study of synthetic and natural food colors effect on biochemical and immunity parameters - Shakoor, Sadaf; Ismail, Amin; Sabran, Mohd Redzwan; Mohtarrudin, Norhafizah; Kaka, Ubedullah; Nadeem, Muhammad (Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, 2021)
Incorporation of the coloring agent, tartrazine and curcumin affects healthy physiological system leading to changes in hematology, biochemistry and enzymatic activity. Consequences of oral administration of tartrazine and curcumin were explored for 15, 30 and 45 days in female adult rat. Two doses were based on the admissible daily intake (ADI) of 9.6 and 96 (high) mg/kg/body weight for tartrazine, 3.85 and 38.5 mg/kg/body weight for curcumin. Phytochemicals such as saponins, glycosides, alkaloids, flavonoids, tannin, carbohydrates and phenolics were present in coloring agents. The renal function tests and lipid profile showed alterations in the values of uric acid, urea, total protein, albumin and cholesterol in all treatment groups. Additionally, the levels of liver enzymes fluctuated after 45 days of treatment with curcumin and tartrazine. Histopathological changes were also recorded in liver and kidney. In contrast, blood biochemistry depicted the significant reduction of RBCs, Hb, MCH, glucose, WBCs, MCHC and LDH at 15, 30 and 45 days. Besides, IgG, IgM and overall antibody GMT at 45 days were significantly increased. Study indicated that ADI and doses up to 10 times of the ADI of food colors intake exerted adverse effects on immune response and altered the biochemical parameters.